2014
DOI: 10.1364/oe.22.024133
|View full text |Cite
|
Sign up to set email alerts
|

Polarization analysis of speckle field below its transverse correlation width : application to surface and bulk scattering

Abstract: An experimental method for accurate polarimetric characterization of speckle field below its transverse correlation width is proposed. Using a polarimetric analyzer, the speckle field under investigation is probed by a set of polarimetric projections describing the full Poincaré sphere surface. Spatial polarimetric variations of the speckle field are thus observed with an accuracy of 1% for each Stokes parameter. Moreover, all the experimental data can be guaranteed by a validity criterion. Using white paper s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…1 and detailed in [10], with a laser diode at the wavelength 532nm illuminating a sheet of paper. The output of the diode which is T EM 00 is sent through a vertical polarizer and a quarter waveplate to generate a right handed circular illumination SOP.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 and detailed in [10], with a laser diode at the wavelength 532nm illuminating a sheet of paper. The output of the diode which is T EM 00 is sent through a vertical polarizer and a quarter waveplate to generate a right handed circular illumination SOP.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in order to achieve a better accuracy for the SOP measurements of a speckle field either produced by surface or bulk scattering, we have developed the State Of Polarization Analysis by Full Projection in the Poincaré space (SOPAFP) method [10].…”
Section: Polarimetric Analysis By Full Projection In the Poincaré Spacementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, experimental measurements have shown that the more the scattered light comes from multiple scattering, the more the SOP are spreading on the Poincaré sphere surface, centered around the illumination SOP [12] [13]. Thus, the effect of the regime of diffusion (from surface to volume) can be modelized through the standard deviation of the relative phase shifts φ , around a mean phase value corresponding to the illumination SOP: π for a vertical incident SOP in the convention chosen here.…”
Section: Polarized Speckle Fields Simulationmentioning
confidence: 99%
“…That description is still valid for partially coherent light and allows us to set the type of scattering continuously from a single to a multiple scatterer. We compare the simulation results with experimental results for surface and multiple scattering [12,13,14,15]. We then study the impact of the imaging point spread function on polarimetry.…”
Section: Introductionmentioning
confidence: 99%